PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA SPPBE PT PARUNG MUSTIKA ABADI - Guntur Ramadhan; Ibnu Sina (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to determine the influence of work discipline and physical work environment on employee performance at SPPBE PT Parung Mustika Abadi. The method used in this research is a quantitative method with a saturated sampling technique totaling 45 respondents. Data analysis includes validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing.The results showed that partially, work discipline has no significant effect on employee performance, as evidenced by the t-count < t-table value of (-0.144 < 1.681) with a significance value of 0.886 > 0.05. Meanwhile, the physical work environment has a positive and significant effect on employee performance with a t-count > t-table value of (5.707 > 1.681) and a significance value of 0.000 < 0.05. Simultaneously, work discipline and physical work environment have a significant effect on employee performance with an F-count > F-table value of (59.604 > 3.220) and a significance value of 0.000 < 0.05. This is supported by the regression equation Y = 5.899 - 0.023X1 + 0.880X2. The coefficient of determination indicates that these two variables contribute 73.9% to employee performance, while the remaining 26.1% is influenced by other factors outside of this study. Keywords: Work Discipline, Physical Work Environment, Employee Performance.